Pemberdayaan Kelompok Ternak Desa Suco Mumbulsari Jember dengan Pelatihan Pembuatan Pupuk Bokashi NPK Teknologi Terbarukan - Susmiati, Yuana; Ari Prasetyo, Dafit; Nurul Karimah, Rinda; Ayu Perwiraningrum, Dhyani; Dora Candra Dewi, Riskha (Politeknik Negeri Jember, 2024)
Suco Village has great potential in the fields of agriculture and animal husbandry. People in Suco village generally raise goats or sheep, and some raise cattle. Livestock in Suco village already uses an integrated livestock concept. Some livestock waste in Suco village is utilized, some is not managed properly. A goat and sheep farm with a capacity of 50 heads will produce around 25 kg of solid manure per day. This will cause environmental and health problems if not managed properly. The training on making organic fertilizer from livestock manure was carried out as part of the 2024 Innovation activities. The training activity aimed to increase knowledge and inspire participants in making organic fertilizer. The activity was attended by all members of the Productive Farm and King Farm livestock groups. During the training, participants increased their knowledge about variations in the composition of organic fertilizers which influence the effectiveness of fertilizers and also how to become a fertilizer entrepreneur, as well as how to market them. The training activities ran smoothly and successfully accompanied by the enthusiasm of the participants. With this activity, it is hoped that it can increase the productivity of organic fertilizer in Suco village, thereby improving its economy.